The small towns residents demand for the urban environment development (the case of sociological research in the Murmansk region) - E. N. Sharova; D. V. Maleus (Вестник университета)
The article looks at the specifics of living conditions in small towns in general, as well as considering their location in one of the Federal subjects of the Arctic zone of Russia. The article also justifies the necessity of developing the urban environment as a significant factor in improving the level and quality of life of the Murmansk region population. Furthermore, it raises the issue about the attitude of small towns residents in this region to the improvement of the territory. The analysis is based on the results of the sociological research conducted in 2021 among the residents of Zaozersk, Kirovsk and Kovdor towns by doing an online survey (301 respondents) and by holding a group discussion (35 participants). Despite the fact that the majority of the surveyed in these small towns represent a positive image of the town, there is an urgent need for the renewal and reconstruction of territories in residential areas, as well as the willingness of residents to directly or indirectly participate in the implementation of measures to develop the urban environment. The main results of the study concretize the needs of the small towns population for the improvement of the territory, and have an applied value for justifying applications for the competition for the best projects in urban environment development in small towns and historical settlements of Russia.